Development of “heart talk” website as a virtual media for counseling - Christanti, Anandita; Defiani, Priska; Dendi, Vidrich; Etti, Keke; Angelina, Maria (Southeast Asian Journal of Technology and Science, 2022)
The development of media technology around the world is growing very rapidly. Nowadays almost everyone has been able to adapt to technology. Website is one of the technologies commonly found, ranging from searching for information, shopping, studying, to playing. There are positive and negative effects of using the website, in this case the researcher maximizes the use of the website in a positive direction for each user. This research was conducted from the stress phenomenon that occurs to many people who do not know where they want to share their stories or complaints, so the researchers made a product in the form of a website that functioned as a place to share stories. has not been disclosed so far. The privacy of every website user is well maintained in order to provide a safe personal story writing experience without having to worry about his identity being known to others. The art of writing and literature counseling theory and the theory of self-healing were selected and applied to serve as independent therapy for website users by writing their own stories. The type of research used is Research and Development (R&D) research, with 34 research subjects. Based on the data that has been obtained then analyzed with relevant theories. Then it was concluded from this study that the use of the website as a medium for sharing stories was found to be useful, interesting, and fun to do.